Decreased circulating follicular regulatory T cells in patients with dilated cardiomyopathy - Liu,Xixi (2021)
Follicular regulatory T cells (Tfr) have critical functions in inflammatory and autoimmune disorders. The main purpose of the current work was to assess Tfr cell frequency in patients with dilated cardiomyopathy (DCM). Flow cytometry showed that, compared with normal controls, DCM cases showed markedly reduced Tfr cell rates and Tfr/Tfh ratios, but significantly increased follicular helper T cell (Tfh) rates. Correlation analysis showed that the Tfr rate in DCM patients was positively correlated with left ventricular ejection fraction (LVEF), and negatively correlated with N-terminal brain natriuretic peptide (NT-proBNP) levels. Lower Foxp3 and higher Bcl-6, ICOS, and PD-1 mRNA expression levels were found in patients with DCM. In addition, plasma interleukin (IL)-6, tumor necrosis factor (TNF)-α, and IL-21 levels were significantly increased in DCM cases. Moreover, IgG and IgG3 levels were also elevated in individuals with DCM. Correlation analysis showed that the Tfr rate in DCM patients was negatively correlated with IgG and IgG3, while the Tfh rate was positively correlated with IgG and IgG3. Changes in circulating Tfr levels may have a critical immunomodulatory function in DCM and may become a new therapeutic target for DCM.